Perbandingan Efektivitas Sacubitril/Valsartan dengan Enalapril pada Pasien Gagal Jantung: Literature Review - Jitayu Sekarininta Mumpun; Laksmi Maharani; Nialiana Endah Endriastuti (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2021)
ARNI (Angiotensin Receptor-Neprilysin Inhibitor) is a new therapy for heart failure patients that have been approved since 2016, which is a combination of sacubitril (Neprilisin Inhibitor) and valsartan (ARB). The aim of this study was to review the comparison of the effectiveness sacubitril/valsartan and enalapril in heart failure patients through a literature review method. Database used were Cochrane and PubMed. Keywords search based on PICO (heart failure, sacubitril/valsartan or LCZ696, enalapril, and efficacy or effectiveness). The inclusion criteria were articles in English, available in full text and free access, published in 2010-2020, and RCT. The exclusion criteria were review articles. The searching was conducted from 10 July to 23 July 2020 and 20 December 2020. From this searching, researcher obtained 160 articles, after the process of selection and eligibility, 16 articles were included in the inclusion criteria as primary articles, and 2 articles were included as secondary articles. Studies showed that sacubitril/valsartan reduces the incidence of readmission and has a better QoL score than enalapril, and also decreases the risk of death. According to primary research of PARADIGM-HF and 15 advanced analysis article, it’s known that the usage of sacubitril/valsartan is more beneficial than enalapril in heart failure patients.